2012
DOI: 10.1021/ol203439g
|View full text |Cite
|
Sign up to set email alerts
|

Selenide Ions as Catalysts for Homo- and Crossed-Tishchenko Reactions of Expanded Scope

Abstract: Selenide ions have been shown to catalyze the Tishchenko reaction for the first time. These catalysts are superior to previously reported thiolate analogues and promote the disproportionation of aldehydes with increased reaction rates and broader scope at lower catalyst loadings and temperatures. Significantly improved catalyst performance was also observed in the aryl selenide mediated crossed intermolecular Tishchenko reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…7 Due to the propensity of nonchelating aldehydes to engage in decarbonylation, 810 Tishchenko dimerizations, 5 and aldol condensations, inter molecular hydroacylations are considerably more challenging. 1113 Herein, we report the design and development of the first enantioselective intermolecular ketone hydroacylation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Due to the propensity of nonchelating aldehydes to engage in decarbonylation, 810 Tishchenko dimerizations, 5 and aldol condensations, inter molecular hydroacylations are considerably more challenging. 1113 Herein, we report the design and development of the first enantioselective intermolecular ketone hydroacylation.…”
Section: Introductionmentioning
confidence: 99%
“…[19] On the basis of these initial studies and literature reports, we propose the mechanism shown in Scheme 6. [20] Ketone 3 d binds to nickel to form complex 8 a, which can coordinate to an aldehyde (1) to give intermediate 8 b. Oxidative addition to the aldehyde CÀH bond generates 8 c, which reduces the hydrogen acceptor 3 d to yield acyl nickel alkoxide 8 d. [21] Ligand exchange with the nucleophile affords 8 e, and reductive elimination provides the final product. Coordination of ketone 3 d may occur prior to [22] or immediately after reductive elimination.…”
mentioning
confidence: 99%
“…This reaction exemplifies an atom-efficient synthesis of esters and it is industrially viable. A large number of compounds containing main group [28] [19a]. To the best of our knowledge, there have been no reports on bis(guanidinate) magnesium and calcium compounds use as catalysts for the Tishchenko reaction.…”
Section: Catalytic Activitymentioning
confidence: 99%